A retrospective comparison of programmed intermittent epidural bolus with continuous epidural infusion for maintenance of labor analgesia. (2nd August 2016) - Tien, Michael; Allen, Terrence K.; Mauritz, Amy; Habib, Ashraf S.
Abstract: Objective: To assess whether maintenance of labor epidural analgesia using programmed intermittent epidural bolus (PIEB) is associated with reduced local anesthetic (LA) consumption, patient-controlled epidural analgesia (PCEA) use, and rescue analgesia requirements compared to continuous epidural infusion (CEI). Research design and methods: This is a retrospective study at an academic university medical center. Women receiving epidural labor analgesia from March to July of 2015 were identified and categorized into three groups: 1) CEI 5 mL/hr, 2) PIEB 5 mL/60 minutes, 3) PIEB 3 mL/30 minutes. The LA consisted of bupivacaine 0.125 mg/mL and fentanyl 2 μg/mL. All patients had similar PCEA settings. Data were collected on pattern of LA usage, obstetric outcomes and Bromage scores. Main outcome measures: The primary endpoint was total volume of LA consumed per hour. Secondary outcomes included need for clinician boluses, pattern of PCEA use, degree of motor blockade and delivery mode. Results: We included 528 patients (262 had CEI, 162 had PIEB 5 mL/60 minutes, and 104 had PIEB 3 mL/30 minutes). Median LA consumed was 10.3, 9.5, and 9.7 mL/hr, respectively ( p  = 0.10). There were no differences in PCEA attempts or rescue clinician boluses, but PCEA volume ( p  = 0.03) and ratio of PCEA attempts/given ( p  < 0.01) were significantly different among the groups. Patients receiving PIEB 3 mL/30 minutes used lower PCEA volume than patients receiving CEI ( p  = 0.04). Patients with PIEB 5 mL/60 minutes and PIEB 3 mL/30 minutes had a higher ratio of PCEA attempts/given than CEI patients ( p  = 0.01 and p  < 0.01, respectively). There were no differences in Bromage scores ( p  = 0.14) or delivery mode ( p  = 0.55) among the groups. Conclusions: The epidural maintenance regimen used (CEI vs. PIEB) was not associated with differences in LA consumption, motor blockade or delivery mode. Main limitations of the study include its single center retrospective design and the fact that patients were not randomized to treatment groups.